Rancang Bangun Aplikasi Pengelolaan Pengaduan Pemeliharaan Aset Pada Politeknik Negeri Samarinda - Alfat Fauzang Haniar; Bambang Cahyono; Yusni Nyura (CV MEDAN TEKNO SOLUSI, 2026)
Asset maintenance is an important element to ensure smooth operations and service quality in educational institutions. Obstacles often arise in the management of asset repair complaints, especially if the process is still done manually. This study aims to design and build an Android-based asset maintenance complaint management application using the Kotlin programming language. This application uses the Firebase Realtime Database for real-time data management and is developed through the Android Studio platform. The test results show that this application is able to increase the efficiency and effectiveness of the complaint reporting and monitoring process. With this application, users can report asset damage in real-time, monitor repair status, and access complaint history easily.